Caracterização morfológica e sedimentologica da plataforma, continental brasileira adjacente aos municípios de Fortim, Aracati e Icapuí- CE - Oliveira, Patricia Reis Alencar (2009)
The study area is located on the Brazilian Continental Shelf adjacent to Ceará State, inserted in the submerged Potiguar Basin. This area was submitted to extensional efforts during Upper Cretaceous, associated to the begining of the rifting that resulted in African and South American Continent separation. The main goal of this research was to better understand the sedimentary and geomorphological characteristics of the continental shelf adjacent to Fortim, Aracati and Icapuí (Ceará State). The used data base included geophysical (sides scan sonar and bathymetry studies) and sedimentological survey, associated to satellite image processing and interpretation. Inferences about suspended material and longshore drift was possible using satellite images, and differente bedforms were characterized such as: different kinds of dunes (longitudinal, cross and oblique), bioclastic banks, paleochannels, flat and rock bottom. The researched area comprehended about 2509,13 km2, where 6 different sedimentary facies, based on sediment composition and texture, could be recognized, such as: Bioclastic Sand, Siliciclastic Sand, Biosiliciclastic Sand, Bioclastic gravel, Biosiliciclastic sand with granule and gravel, and Silicibioclastic sand with granule and gravel. The integration of bathymetric, satellite image, side scan sonar and sedimentological data allow us a better characterization of this continental shelf area, as to advance in the knowledge of the continental shelf of the state of Ceara, a very important area to the oil industry because of its potential exploration and e exploitation, and to environmental survey as well